Current pharmacological management of idiopathic overactive bladder in children in the UK: a national survey of practice. Issue 1 (February 2020) - Melling, Charlotte Victoria; Goyal, Anju
Summary: Background: Children with daytime urinary incontinence secondary to idiopathic overactive bladder (IOAB) commonly present to paediatric urologists following failure of standard urotherapy and/or 1st-line anticholinergics. Off-label oral medications and intravesical botulinum toxin A (BtA) are being increasingly used for treatment-refractory IOAB, despite the paucity of high-quality evidence and guidelines. Knowledge of contemporary paediatric urologists' practice allows specialists to keep up-to-date with current trends in the management of IOAB in children. Objectives: 1. To present an analysis of contemporary tertiary management of IOAB in children and 2. to highlight current trends in practice and identify areas of high variability in care for targeted research. Methods: Paediatric urologists (55 individuals) who attended the 2018 national British Association of Paediatric Urologists (BAPU) congress responded to a 20-question survey presented at the congress. Respondents could submit one answer per question, and one survey was taken per respondent, using secure software to disable any manipulation. Answers were analysed prospectively by a single reviewer. Results: Of UK paediatric urologists, 98% regularly manage children with IOAB, 48% use 48-h frequency/volume charts and others use three or seven-day bladder diaries to aid diagnosis. Oxybutynin is the 1st-line therapy for 85%, 2nd-line is tolterodine (53%), and 3rd-line is solifenacin (41%). Mirabegron is used either alone or in combination with solifenacin as 4th-line management by 55%. Those who use intravesical Botulinum toxin A (BtA) accounted for 81% and 84% of these perform invasive urodynamic assessment prior to BtA administration. Post-BtA, assessment was clinical in 18%, 24% use invasive urodynamics, whereas uroflowmetry is preferred by 58%. Of the paediatric urologists, 72% believe the most clinically significant outcome of treatment is patient-reported improvement. Treatment success is defined variably: 49% define success as completely dry, whereas 35% accept a 90% improvement as success. Conclusions: Off-label medications are being used widely either alone or in combination by paediatric urologists. In oral therapy-resistant IOAB, BtA is being used by the majority of specialists, usually after formal urodynamic assessment. However, post-BtA assessment and evaluation of treatment success for IOAB are variable. Summary Fig. Image 1